Individual cell-only bioink and photocurable supporting medium for 3D printing and generation of engineered tissues with complex geometries. Issue 8 (24th June 2019) - Jeon, Oju; Lee, Yu Bin; Jeong, Hyoen; Lee, Sang Jin; Wells, Derrick; Alsberg, Eben
Abstract : Functional tissues with complex geometries can be engineered by 3D bioprinting individual cell-only bioinks into a photocrosslinkable microgel support bath, which permits structural control over cellular condensation formation and long-term culture. Abstract : Scaffold-free engineering of three-dimensional (3D) tissue has focused on building sophisticated structures to achieve functional constructs. Although the development of advanced manufacturing techniques such as 3D printing has brought remarkable capabilities to the field of tissue engineering, creating and culturing individual cell-only based high-resolution tissues with complex geometries without an intervening biomaterial scaffold while maintaining the resulting constructs' shape and architecture over time has not been achieved to date. In this report, we introduce a cell printing platform which addresses the aforementioned challenge and permits 3D printing and long-term culture of a living cell-only bioink lacking a biomaterial carrier for functional tissue formation. A biodegradable and photocrosslinkable microgel supporting bath serves initially as a fluid, allowing free movement of the printing nozzle for high-resolution cell extrusion, while also presenting solid-like properties to sustain the structure of the printed constructs. The printed human stem cells, which are the only component of the bioink, couple together via transmembrane adhesion proteins and differentiate down tissue-specific lineages while being cultured in a further photocrosslinked supporting bath to form bone and cartilage tissue with precisely controlled structure. Collectively, this system, which is applicable to general 3D printing strategies, is a paradigm shift for printing of scaffold-free individual cells, cellular condensations and organoids, and may have far reaching impact in the fields of regenerative medicine, drug screening, and developmental biology.